New Insight into Immunity and Immunopathology of Rickettsial Diseases. (5th July 2011) - Mansueto, Pasquale; Vitale, Giustina; Cascio, Antonio; Seidita, Aurelio; Pepe, Ilenia; Carroccio, Antonio; di Rosa, Salvatore; Rini, Giovam Battista; Cillari, Enrico; Walker, David H.
Abstract : Human rickettsial diseases comprise a variety of clinical entities caused by microorganisms belonging to the genera Rickettsia, Orientia, Ehrlichia, and Anaplasma . These microorganisms are characterized by a strictly intracellular location which has, for long, impaired their detailed study. In this paper, the critical steps taken by these microorganisms to play their pathogenic roles are discussed in detail on the basis of recent advances in our understanding of molecular Rickettsia -host interactions, preferential target cells, virulence mechanisms, three-dimensional structures of bacteria effector proteins, upstream signalling pathways and signal transduction systems, and modulation of gene expression. The roles of innate and adaptive immune responses are discussed, and potential new targets for therapies to block host-pathogen interactions and pathogen virulence mechanisms are considered.